Support Strategy for the Social Appropriation of New Technologies in Gulupa-producing Communities in Colombia (2023)
This article presents a proposal for a support strategy for the social appropriation of new technologies in agricultural communities. This strategy is based on the approach of linear processes in which traditional actors (academy, state, companies) develop a technology to solve a problem and then transfer it to users. The strategy is grounded on the concepts of social practice, weak social appropriation of science and technology (ASCyTD, by its acronym in Spanish) and strong social appropriation of science and technology (ASCyTF, by its acronym in Spanish), and is illustrated with an example of how it could be applied in the appropriation of a technology to determine three stages of ripening of the gulupa fruit (Passifloras edulis Sims). To obtain the information required in the example on traditional knowledge, scientific knowledge and possible technologies that guide human actions in the agricultural practice of harvesting gulupas fruits, which are part of the culture of the agents receiving the technology in question, a survey was conducted among 52 farmers in some municipalities of Cundinamarca, Colombia. The interviews showed, among other things, that even though 83 % are in favor of the use of technology in the practice of harvesting, the task is still guided by the "feel" (hardness, weight and size) and "eyesight" (colors of the peel). This work is expected to contribute to the agricultural communities with the initiatives of social transfer of new technologies specifically proposed by the academy.